EFFICIENCY OF WINTER WHEAT CULTIVATION DEPENDING ON SOWING DATES AND FERTILIZATION IN THE NORTHERN STEPPE OF UKRAINE - Astakhova, Ya. V.; Gasanova, I. I.; Kulyk, A. O. (Scientific Progress & Innovations, 2021)
The article presents the results of three-year research regarding the influence of sowing dates and mineral nutrition on the yield and economic efficiency of cultivating Lastivka Odeska, Holubka Odeska soft winter wheat varieties and Burshtyn hard variety sown on weed free fallow and after spring barley. Winter wheat was sown on three dates – September 7, 22, and October 7. Fertilization options were the following: 1 – without fertilizers (control); 2 – pre-sowing application of fertilizers (after weed free fallow – N30P60K30, after spring barley – N60P60K30 ); 3 – fertilization system (against the background of pre-sowing mineral fertilizers’ application: after weed free fallow N30 additional fertilizing locally at the end of plants tillering phase, after spring barley – N30 in early spring on frozen-melted soil (FMS) + N30 locally). Based on the research, it has been established that the highest yields and net profit at cultivating all winter wheat varieties (both on weed free fallow and after spring barley) are provided by applying crop fertilization system which includes pre-sowing application of complete fertilizer and spring nitrogen additional fertilizing. The mineral fertilizers’ application after both predecessors helped to increase yields and improve the grain class: in soft winter wheat – up to the second or third, and in hard winter wheat – up to the first class in some cases. In the experiments, the minimum values of economic efficiency for all winter wheat varieties were obtained in “no fertilizers” variants. Higher economic efficiency of winter wheat cultivation after both predecessors in Lastivka Odeska and Burshtyn varieties was obtained at the optimal sowing date (September 22), and in Holubka Odeska variety – at the admissible early date (September 7) and the optimal date (September 22). After spring barley, the highest cultivation efficiency was provided by Holubka Odeska variety, which on fertilized plots formed the grain of the third-class quality with the yield of 4.81–6.05 t/ha and production profitability of 121–145 %. The best economic indicators against the background of pre-sowing application of N60P60K30 complete fertilizer were observed in the variant with nitrogen additional fertilizing of winter wheat in two terms: 1) N30 in the early spring on frozen-melted soil and 2) N30 locally at the end of tillering phase.